Between East and West: Akira Kurosawa (KULT_online, 2015)
Akira Kurosawa is one of the big shots in the history of cinema. His movies have influenced directors in numerous countries, and continue to do so. Now, at last, a German monograph about the life and works of the master that is truly worth reading, by Marcus Stiglegger. Thematically, Kurosawa's work shows a strong western influence but, at the same time, is strongly based on Japanese culture. It was especially ways of dealing with death and the process of dying that fascinated the filmmaker, which Stiglegger weaves into the title of this book: "Die Ästhetik des langen Abschieds".